Activating the legal seclusion system as a mechanism for rehabilitating detainees under comparative penal systems - Hayet, Benmessaoud; Rachid, Larouci (The International tax journal, 2026)
Some human rights and freedoms are considered fundamental to human existence. They are inherent in any person because of his humanity and are based on respect for the dignity and value of every person. They are not privileges granted by the state or the authorities. In return, no arbitrary authority has the right to remove them Perhaps the most important of these rights is the right of the imprisoned person to practice his sexual life normally with his wife, given that he is a person who violated the legal rules and whose freedom was taken away in order to be reformed and socially reintegrated, but this does not mean that his natural rights as a human being are taken away Thus, the view will shift to prison as a place to re-evaluate the offender's behavior instead of considering this detention as retaliation, especially since the issue of humanizing punishment and the continuous search for alternatives to it is still the subject of widespread jurisprudential controversy by proposing several different theories that have developed in parallel with the international system towards greater dedication to human rights, which are considered an essential tool for his social rehabilitation.